Analisis Penanganan Guest Complaint dalam Upaya Meningkatkan Kepuasan Pelanggan (Studi Kasus F&B Service pada Matra 21 Resto, Grand Menteng Hotel Matraman) - Suwarta, Firdaus (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Complaints often arise due to customer dissatisfaction and disappointment resulting from a company’s failure to understand their needs and desires. With the right response, these complaints can be effectively addressed, leading to customer satisfaction. This research aims to understand the handling procedures carried out by the f&b service department at Matra 21 restaurant in Grand Kemang Hotel Matraman. It also seeks to identify the efforts and obstacles encountered when dealing with complaints at Matra 21 restaurant. The research employs a qualitative descriptive approach, utilizing data collection methods such as observation, interviews and documentation. Informants participating in this study include Matra 21 restaurant staff, guests who have experienced the products and service at Matra 21 restaurant, as well as academicians. The findings of this research indicate that complaint handling by Matra 21 restaurant staff aligns with established standard operating procedures (SOP). Efforts such as daily guest feedback and guest preferences are like ILEAD (identify, listen, empathy, apologize and decide). However, there are factors hindering complaint resolution, such as guests requesting nonstandard procedures beyond the existing Standard Operating Procedures.